Parental Investment in Children’s Educational Pathways: A Comparative View on Swiss and Migrant Families - Kamm Chantal; Gomensoro Andrés; Heers Marieke; Hupka-Brunner Sandra (Swiss Journal of Sociology, 2023)
What strategies do parents adopt when it comes to realizing the aspirations they have for their children’s educational career? Drawing on a longitudinal and intergenerational mixed-method study, we explore the complex interplay between children’s educational pathways and parental educational aspirations and strategies. We focus on parents of modest social status (with and without migration background) whose children’s educational trajectories have developed successfully.